1989
DOI: 10.1111/j.1944-9720.1989.tb03138.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning Strategies in Foreign Language Instruction

Abstract: This paper summarizes the findings of a three year project which investigated the use of learning strategies by foreign language students and their teachers,1 and suggests specific classroom applications for learning strategy instruction. Three studies were conducted under this project: (a) a Descriptive Study, which identified learning strategies used in studying foreign languages, (b) a Longitudinal Study, which identified differences in the strategy use of effective and ineffective language learners and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
226
4
21

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(267 citation statements)
references
References 12 publications
16
226
4
21
Order By: Relevance
“…This is similar to the results of studies such as those by Chamot and Kupper (1989), Goh and Kwah (1997), and Magogwe and Oliver (2007). It may be that like students in Oxford"s (1993) study, students in Iran are largely unaware of the potential of socioaffective strategies.…”
Section: Discussionsupporting
confidence: 77%
“…This is similar to the results of studies such as those by Chamot and Kupper (1989), Goh and Kwah (1997), and Magogwe and Oliver (2007). It may be that like students in Oxford"s (1993) study, students in Iran are largely unaware of the potential of socioaffective strategies.…”
Section: Discussionsupporting
confidence: 77%
“…La menor utilización de esta categoría de estrategias, se puede deber al hecho de que el nivel de lengua extranjera que poseen los sujetos objetos de estudio no es un nivel elemental. Otra posible explicación a este hecho, pudiera ser que no son conscientes de la frecuencia de su uso, como ocurrió en la investigación realizada por Chamot & Kupper (1989).…”
Section: Tabla 4 Frecuencia De Uso De Las 6 Categorías De Estrategiasunclassified
“…These traits are listed as the following: Furthermore, Oxford (1994) listed some important findings which support the effectiveness of using language learning strategies to enhance learners' proficiency. These findings are listed as following: (1) appropriate language learning strategy use can improve leaners' language proficiency (Oxford et al, 1993;Thompson & Rubin, 1993), (2) successful language learners are usually using language learning strategies tactically to reach the requirement for various language tasks (Chamot & Kupper, 1989), and they can easily explicate their various engaged language strategies (O'Malley & Chamot, 1990); (3) both cognitive and metacognitive strategies are often employed together to support each other. Combination of two or more strategies helps in language learning (O'Malley & Chamot, 1990); (4) certain language learning strategies are bonded together for specific language tasks (Chamot & Kupper, 1989); (5) language learners don't pay attention to their feelings and social relationships with others; thus, few studies on social and affective strategies are found in L2 research (Oxford, 1994).…”
Section: The Relevant Studies Of Language Learning Strategiesmentioning
confidence: 99%
“…Language learning strategies are being identified as distinct behaviors and mental processes used among learners to help assist language acquisition (Park, 2011;Weinstein & Mayer, 1986). Various studies have proven the language strategies impact learning L2 (Bialystok, 1981;Chamot & Kupper, 1989;Cohen, 1990;Naiman, Frohlich & Todesco, 1975). Good language learners are identified as the following: active and accurate guessers, strong-motivated communicators, mentally-independent individuals, brave persons who make mistakes, people who tend to analyzing language-patterns, and enjoy taking any opportunities to use the language, monitoring others' talks, and paying close attentions to meanings (Oxford, 1994;Rubin, 1975).…”
Section: Background Of the Studymentioning
confidence: 99%